1. PK = sqrt[(x+1)^2 + (y-3)^2]

square of the distance = PK^2 = (x+1)^2 + (y-3)^2

2. Logically, distance of P from y=0 is always a vertical distance as y=0 is a horizontal line. Therefore, distance of P from the line y=0:

|y-0| = |y|

Square of the distance = y^2

3. From the first two parts, you have the distance of PK and distance of P from y=0

Equating the two:

(x+1)^2 + (y-3)^2 = y^2

(x+1)^2 + y^2 - 6y + 9 = y^2

(x+1)^2 = 6y - 9

(x+1)^2 = 6(y - 3/2)

Therefore the locus of P is a parabola with vertex (-1, 3/2)

## Bookmarks